UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK MENGGUNAKAN MASALAH OPEN ENDED - Listianto, Gandi; Setianingsih, Rini; Sugianto, Agus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The ability to think creatively is one of the abilities that every student must have from as early as possible, because if the ability to think creatively is not trained from an early age then the development of students' thinking abilities will not develop. With the importance of creative thinking abilities, this research aims to improve the creative thinking abilities of students in class VII-G of SMP Negeri 2 Pamekasan with the 2023/2024 even semester academic year with triangle and quadrilateral material by applying an open ended problem approach. This research also explains the criteria for creative thinking abilities using four criteria, including: 1) Fluency, 2) Flexibility, 3) Originality, and 4) Detailedness (elaboration). The research method used is classroom action research (PTK) which consists of planning, implementation, observation and reflection. Data collection was carried out by means of observation and tests. Observations and tests were carried out to determine the level of students' creative thinking abilities during the learning process using an ongoing open ended problem approach with the subjects in this research being students in class VII-G of SMP Negeri 2 Pamekasan. The results of this research are that there is an increase in teacher (researcher) activity when carrying out teaching and learning activities from cycle I to cycle II, cycle II to cycle III, and cycle III to cycle IV. Apart from that, there has been an increase in the activity of teachers (researchers) and students in implementing learning and it is also in accordance with the learning implementation plan in the teaching module in increasing students' creative thinking abilities with triangle and quadrilateral material by applying an open ended problem approach.